2020
DOI: 10.3390/bs10050089
|View full text |Cite
|
Sign up to set email alerts
|

Survey for Assessment of a Person’s Legal Consciousness: Development and Preliminary Validation

Abstract: The results of the development and preliminary assessment of the psychometric properties of the questionnaire of legal consciousness of a person are presented. Theoretical justification is given for the structure of the questionnaire containing six subscales. One scale relates to the individual’s awareness of constitutional rights and freedoms, enshrined in the Universal Declaration of Human Rights and the Constitution of the Russian Federation (personal, economic, political, cultural and social rights). The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Thus, we focused on the issue of legal consciousness. As a concept in legal science, assessing legal consciousness is complicated, as it involves a cognitive component as well as emotional and behavioral elements [ 52 ]. Horák et al reviewed 2,054 articles, included 156 relevant articles and identified six components of legal consciousness including general knowledge, skills, specific knowledge, attitudes, trust, and identity [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we focused on the issue of legal consciousness. As a concept in legal science, assessing legal consciousness is complicated, as it involves a cognitive component as well as emotional and behavioral elements [ 52 ]. Horák et al reviewed 2,054 articles, included 156 relevant articles and identified six components of legal consciousness including general knowledge, skills, specific knowledge, attitudes, trust, and identity [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interview questionnaires are referenced from an existing study by Molotova et al (2020), modified in order to cater to the study. Its properties are inclusive of psychometric aspects and the topic expertise of the respondent developed to achieve the six segmented goals all aimed to comprehend the respondents' perspectives, approaches, and understanding.…”
Section: Sociolegalmentioning
confidence: 99%
“…There is currently no appropriate and accurate toolkit in a quantitative form that provides a holistic purview of obtaining the enumerated objectives. The questionnaire developed by Molotova et al (2020), has been examined and furnished to administer the review and analysis of Article 247 in accordance with the principles of policy reform.…”
Section: Sociolegalmentioning
confidence: 99%
“…Legal ideology is understood as a system of legal knowledge whereas legal psychology is regarded as a combination of feelings, beliefs, habits, and motives of legally volitional actions. This was further developed into a three-component-construct: cognitive (legal concepts and knowledge, cognitive assessment of legal phenomena), affective (emotional assessment of legal phenomena), and behavioral (intention to behave in a certain way in legal situations; Molotova et al, 2020). More complex models were also proposed, such as a four-component model of legal consciousness introduced by Shchegortsev (1981), which includes a substantive component (knowledge and ideas of law), evaluative component (assessment of legal phenomena), behavioral component (behavior and activity of people in legal situations) and energy (emotions and feelings of people experienced in a meaningful situation); and a six-component model was proposed by Horák et al (2021).…”
Section: The Legal Emotion a Key Component Of Legal Consciousnessmentioning
confidence: 99%